Development of a Caregiver‐Reported Experience Measure for Pediatric Hospital‐to‐Home Transitions. (8th May 2018) - Desai, Arti D.; Jacob‐Files, Elizabeth A.; Lowry, Sarah J.; Opel, Douglas J.; Mangione‐Smith, Rita; Britto, Maria T.; Howard, Waylon J.
Abstract : Objective: To develop and test a caregiver‐reported experience measure for pediatric hospital‐to‐home transitions. Data Sources/Study Setting: Primary data were collected between 07/2014 and 05/2015 from caregivers within 2–8 weeks of their child's discharge from a tertiary care children's hospital. Study Design/Data Collection: We used a step‐wise approach to developing the measure that included drafting de novo survey items based on caregiver interviews ( n = 18), pretesting items using cognitive interviews ( n = 18), and pilot testing revised items among an independent sample of caregivers ( n = 500). Item reduction statistics and confirmatory factor analysis (CFA) were performed on a test sample of the pilot data to refine the measure, followed by CFA on the validation sample to test the final measure model fit. Principal Findings: Of 46 initial survey items, 19 were removed after pretesting and 19 were removed after conducting item statistics and CFA. This resulted in an eight‐item measure with two domains: transition preparation (four items) and transition support (four items). Survey items assess the quality of discharge instructions, access to needed support and resources, care coordination, and follow‐up care. Practical fit indices demonstrated an acceptable model fit: χ 2 = 28.3 ( df = 19); root‐mean‐square error of approximation = 0.04; comparative fit index = 0.99; and Tucker–Lewis index = 0.98. Conclusions: An eight‐item caregiver‐reported experience measure to evaluate hospital‐to‐home transition outcomes in pediatric populations demonstrated acceptable content validity and psychometric properties.